Biochemical composition and antioxidant activity affected by spraying potassium sulfate in black grape (Vitis vinifera L. cv. Rasha). (22nd June 2018) - Zareei, Elnaz; Javadi, Taimoor; Aryal, Rishi
Abstract: BACKGROUND: The physiological and metabolic processes involved with grapevine growth and production are influenced by key macro‐ and micronutrients. Potassium is an essential plant nutrient that affects growth and fruit quality. In this study, the impact of foliar spraying of potassium sulfate (K2 SO4 ) on qualitative characteristics of grape berries was evaluated in the cultivar 'Rasha', a commonly cultivated cultivar in Kurdistan province of Iran. Leaves of the fully grown vines were sprayed with each of the 1.5 and 3 g L −1 K2 SO4 solutions once (1 month after petal senescence) and twice (15 days after first spraying). The control plants were sprayed with distilled water. Various biochemical contents and enzyme activities on the ripe berries were analyzed. RESULTS: Significant increases in anthocyanin, total protein content, and antioxidant enzyme activities were observed in the berries treated twice with 3 g L −1 K2 SO4 . Concentrations of total carbohydrate, phenol, and antioxidant activity in berries sprayed with K2 SO4 were higher than in the controls. We observed a strong correlation between antioxidant activity and different phenolic compounds. CONCLUSION: These findings suggest that K2 SO4 treatment influences biosynthesis of phenolic compounds and antioxidant enzymes. Thus, treatment by K2 SO4 could improve nutritional and qualitative attributes of grape. © 2018 Society of Chemical Industry